Oracle VM implementation and administration guide - Whalen, Edward (New York McGraw-Hill, 2011)
This Oracle Press guide provides practical implementation and administration information on Oracle's new, free entry into the virtualization market, Oracle VM.
Part I: Introduction -- Chapter 1: Introduction to virtualization -- Chapter 2: What is Oracle VM? -- Chapter 3: Oracle VM architecture -- Chapter 4: Oracle VM lifecycle management -- Chapter 5: Planning and sizing the enterprise VM Farm -- Part II: Installing and configuring Oracle VM -- Chapter 6: Installing the Oracle VM server -- Chapter 7: Installing and configuring Oracle VM manager -- Chapter 8: Configuring the Oracle VM management pack -- Chapter 9: Installing and configuring the Oracle VM CLI -- Chapter 10: Configuring the VM Server Network -- Chapter 11: Configuring the VM Server Storage -- Part III: Managing Oracle VM servers and guests -- Chapter 12: Creating server pools and servers -- Chapter 13: Configuring server resources -- Chapter 14: Managing and tuning the Virtual Machine server -- Part IV: Installing and configuring the Guest OS -- Chapter 15: Creating templates -- Chapter 16: Using templates to create Virtual Machines and configuring resources -- Chapter 17: Creating Virtual Machines manually -- Chapter 18: Converting other virtual images to Oracle VM -- Chapter 19: Managing the VM environment and Virtual Machines -- Chapter 20: Virtualization summary and best practices practices -- Part V: Appendixes and glossary -- Appendix A: Configuring Linux support functions -- Appendix B: Oracle VM log files -- Glossary -- Index.
Keywords: Oracle (Computer file).; Virtual computer systems